Causal relationship between inflammatory bowel disease and sex: a Mendelian randomization study - Kaiwen Wang; Yu Lou; Shunjie Tian; Zhihui Tao; Zhihui Tao (Frontiers in Endocrinology)
ObjectiveThe aim of this study was to investigate the bidirectional causal relationship between sex hormones and IBD through a two-sample bidirectional Mendelian randomization (MR) study.MethodsBased on Genome-Wide Association Study (GWAS) pooled data on SHBG, total testosterone, bioavailable testosterone, estradiol, and IBD in a European population, we performed two-sample bidirectional MR analyses using single nucleotide polymorphisms (SNPs) as instrumental variables. We used inverse variance weighting (IVW), weighted median, weighted mode, and MR-Egger to assess bidirectional causality between sex hormones and IBD.ResultsThere was no causal relationship between sex hormones and IBD in women (P > 0.05), and there was a causal and positive correlation between SHBG and testosterone and IBD in men.The OR for SHBG was 1.22 (95% CI: 1.09-1.37, P = 0.0004), and for testosterone was 1.20 (95% CI: 1.04-1.39, P = 0.0145).IBD did not significantly interact with female sex hormones but resulted in a decrease in SHBG (OR = 1.02, 95% CI: 1.00-1.04, P = 0.0195) and testosterone (OR = 1.01, 95% CI: 1.00 -1.02, P = 0.0200) in men.ConclusionThere is no causal relationship between female sex hormones and IBD, but male SHBG and testosterone are positively correlated with the risk of IBD and IBD promotes elevated levels of SHBG and testosterone in males, suggesting that sex hormones play different roles in IBD patients of different sexes.